Factors promoting exclusive breastfeeding at a public health facility in Windhoek Namibia: A descriptive comparative study - Ruusa Megameno Nangolo; Anneline Robertson; Talitha Crowley (Elsevier, 2023)
Introduction: Exclusive breastfeeding (EBF) refers to the practice of giving an infant breast milk only up to the age of six months, except for oral rehydration solutions or drops/syrups of vitamins, minerals or medicines. Globally and in Namibia, EBF rates remain well below the 70% World Health Organisation (WHO) target. Objective: This study aimed to investigate factors that promote EBF amongst mothers at a public health facility in Windhoek, Namibia. Methods and materials: A quantitative comparative descriptive design was used. Women aged 18 and above with infants aged 0 to 6 months attending a public health facility (n = 270) in Windhoek, Namibia, were selected using non-probability consecutive sampling. A structured self-administered questionnaire was used to collect data on socio-demographic, economic, knowledge, psychosocial, biophysical and sociocultural factors. Data was analysed using descriptive statistics and logistic regression. Results: A large majority of participants practised EBF (87.8 %, n = 237). No significant socio-demographic, economic, knowledge, psychosocial or sociocultural predictors of EBF were identified. Having more than two pregnancies and more than two children were found to be statistically significant predictors of EBF (OR = 2.9, CI = 1.0 to 8.4, p = 0.05), (OR = 3.2, CI = 1.0 to 10.1, p = 0.05) Conclusion: EBF practice in this study is high, suggesting that mothers who access maternal healthcare services may be more likely to practice EBF. Primiparous mothers need increased support to promote EBF.